Maple Terrace - Van Sciver, Noah (Uncivilized Books, 2024)
From a multiple-award-winning cartoonist, Noah Van Sciver, comes Maple Terrace, a new autobiographical graphic novel. Based on the author's childhood, Maple Terrace unfolds a tale of big money comic-collecting craze of the early 90s as seen from the ground floor. In a time when superheroes were oversized, adorned with massive guns, and countless pouches, comic books were currency! Young investors struggled to collect every cover gimmick under the sun--embossed-metallic ink-holographic foil--hoping they someday would pay for their college education. Brutally hilarious, Maple Terrace shines a light on the strange intersection between poverty and speculative comic book craze of the 90s.